Cell death - Melino, Gerry; Vaux, David (Wiley-Blackwell, 2010)
* Contains 29 self-contained, peer-reviewed articles written by leading scientists in each field. * Provides a comprehensive overview on the research of programmed cell death. * Edited by leaders in the field. * Clearly written and illustrated articles. * Full colour throughout.